Active Cycle Of Breathing Technique Terhadap Fungsi Paru pada Pasien Paska Operasi Bedah Jantung: Active Cycle of Breathing Technique on Pulmonary Function in Patients Post Cardiac Surgery - Fakrul Ardiansyah; Elly Nurachmah; Muhamad Adam (Fakultas Keperawatan Universitas Andalas, 2021)
The pulmonary complication after cardiac surgery is estimated to be 2-4%. These complications increase the length of hospital stay and increase cost. Postoperative cardiac surgery care focuses on pulmonary function with active cycle of breathing technique (ACBT). This study aimed to identify the effectiveness of ACBT in recovery pulmonary function in postoperative cardiac surgery. This study used pra experiment method involving 30 respondents with purposive sampling technique in adult surgery intensive care unit and Surgical ward. This group applies ACBT for 4 days: 2x/day, duration 15 minutes/session on 1st and 2nd day after surgery; 1x/day, duration 15 minutes/session on 3rd and 4th day after surgery. The Peak Expiratory Flow Rate is evaluated with Peak flow meter tools. The pretest data were obtainedd on the pre operation and the post test data were obtained on the 3rd day after surgery. This data analyzies with distribution mean and wilcoxon. The result distribution means of Peak Expiratory Flow (PEF) pretest is 420,33 l/minute and the post test is 432,33 l/minute. The result of wilcoxon test is p=0,001< α=0,05, it is show that significant effect in PEF (Peak Expiratory Flow) pre, 3rd day PEF. ACBT consists of deep breathing and hold breathing, so the air flow easier and the discharge mucous, on the last step is the huffing technique. It is not required stretgh to discharge mucous and reduce pain. ACBT can be used as a nursing intervention for airway management to recovery pulmonary function in postoperative cardiac surgery.